Sequence and functional characterization of a public HIV-specific antibody clonotype - Amyn A. Murji; Nagarajan Raju; Juliana S. Qin; Haajira Kaldine; Katarzyna Janowska; Emilee Friedman Fechter; Rutendo Mapengo; Cathrine Scheepers; Ian Setliff; Priyamvada Acharya; Lynn Morris; Ivelin S. Georgiev (iScience, 2022)
Summary: Public antibody clonotypes shared among multiple individuals have been identified for several pathogens. However, little is known about the determinants of antibody “publicness”. Here, we characterize the sequence and functional properties of antibodies from a public clonotype targeting the CD4 binding site on HIV-1 Env. Our results showed that HIV-1 specificity for the public antibodies studied here, comprising sequences from three individuals, was modulated by the VH, but not VL, germline gene. Non-native pairing of public heavy and light chains from different individuals suggested functional complementation of sequences within this public antibody clonotype. The strength of antigen recognition appeared to be dependent on the specific antibody light chain used, but not on other sequence features such as native-antibody or germline sequence identity. Understanding the determinants of antibody clonotype “publicness” can provide insights into the fundamental rules of host-pathogen interactions at the population level, with implications for clonotype-specific vaccine development.